Development of kinematic simulation system for high-speed press line automated feeding robot. (2nd August 2018) - Zhang, Zhulin; Ding, Dong; Yu, Luchuan; Zhao, Xianjin; Zhang, Jianhua; Zhang, Zhigang; Zhang, Qinhe
High-speed press lines are related to the fierce competition in the automobile industry and rely on continuous high-efficiency automated feeding systems. Kinematic simulation systems have facilitated the improvement of production processes by generating real-time kinematic curves to avoid interference in feeding systems. In this article, a new method based on quintic polynomials in MATLAB and ADAMS is introduced to achieve whole-line planning using a kinematic simulation system for path planning. Furthermore, secondary interface is developed to visualize the kinematic curves and animate the generated whole-line trajectories. The kinematic simulation system was found to improve the efficiency of generating predicted trajectories in joint or Cartesian space and achieved reliable whole-line path planning, including collision inspection and singular point detection, by using parametric modeling and analyzing kinematic curves. Finally, the kinematic simulation system was verified using results of a kinematic analysis and example simulation.